STUDY OF PRESERVATIONDRY SWEET PINEAPPLE (Ananas comous L. Merr) DURING STORAGE - Desy Nofriati (Jurnal Agroindustri, 2013)
Processing fresh pineapple into dried sweet pineapple can preserve product during storage. Durability dry sweet products can be maximized by combining sugar with other preservation techniques such as paesterisasi treatment, enhance sodium benzoate, and packaging technology. The objective the study is to find out durability time product dry sweet pineapple. The study design used experiments making dried sweet pineapple which consists of several stages. There are stripping, washing, cutting, boiling, cooking, soaking, drying and packaging. Drying is done for 3 days under the sun. The durable time have known by observations during storage; dry sweet pineapple with packaging and stored without packaging. Product damage during observed indicated by physical appearance, color and texture. Durability dry sweet pineapple without packaging lower than product with packaging